2014
DOI: 10.1080/09593330.2014.943299
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of sulphamethoxazole by the biochars derived from rice straw and alligator flag

Abstract: The sorption ability of sulphamethoxazole (SMX) by biochar derived from rice straw (RS) and alligator flag (AF) at 600°C was studied to assess the ability of biochar as adsorbent to remove SMX from aqueous solution. The results indicated that sorption of SMX by biochars was well described using the Langmuir equation (R2>0.94), and the maximum sorption parameter (Q) of RS (3650 mg kg(-1)) was much higher than that of AF (1963 mg kg(-1)). Temperature had no effect on SMX sorption by biochars, while thermodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…One option could be to use smaller particle sizes and hydraulic loads. An example of this improvement was demonstrated by Li et al [51], who observed that while the chemical composition of their biochar did not change after crushing it, its efficacy in removing sulphamethoxazole improved significantly. Further, the hydraulic loads may also be lowered during summer when there is increased amount of organic loads.…”
Section: Possible Improvements Of the Systemmentioning
confidence: 91%
“…One option could be to use smaller particle sizes and hydraulic loads. An example of this improvement was demonstrated by Li et al [51], who observed that while the chemical composition of their biochar did not change after crushing it, its efficacy in removing sulphamethoxazole improved significantly. Further, the hydraulic loads may also be lowered during summer when there is increased amount of organic loads.…”
Section: Possible Improvements Of the Systemmentioning
confidence: 91%
“…Feedstocks of animal or human origin may also contain substantial quantities of unmetabolized antibiotics that could lead to the development of antibiotic resistance in the soil microflora on amendment (Ippolito et al, 2012). The fate of antibiotics on charring is largely unknown, even though active sorption of veterinary drugs by biochars has been demonstrated in soil (Jeong et al, 2012) and in water (Li et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the sorption of negative species was controlled by proton exchange, although with a significant role of π-π electron acceptor-acceptor interactions. Li et al [182] investigated the sorption of SMX on biochars derived from rice straw (RS) and alligator flag (AF). The adsorption was well described by the Langmuir isotherm with saturation capacities of 3.65 mg•g −1 with rice straw derived adsorbent.…”
Section: Contaminant Biomass Precursor Synthesis Conditions Biochar Cmentioning
confidence: 99%